Rural tourism marketing: Lavender tourism in Turkey - Giray,Fatma Handan (2019)
ABSTRACT: This study aimed to comprehend rural tourism marketing through the visitors’ eyes and discuss its sustainability. What makes rural tourism marketing more sophisticated and complex is that it is a service marketing, associated with agricultural activities, natural conditions and rural areas, and the main providers have no experience in rural tourism or service marketing. The study investigated perception of visitors in a small village, Kuyucak, in the Southwest part of Turkey, where rural tourism based on lavender production has recently developed. Results of the analysis of 175 questionnaires completed by visitors online showed that more than half of the respondents had heard and got information about the village via social media. Although, the main purpose of their visit was stated as nature/rural experience and recreation/holiday, the primary motivation of the majority was taking and sharing photos via social media tools. Appearance of lavender and previous social media sharing are very important determinants in the decision-making and expectations of visitors. Results of the factor analysis showed that two components composed of the variables regarding pre-visit perception and the physical conditions of the village together explain sixty-five per cent of the overall satisfaction. The most important component in decision making of visitors was found their perception before visiting, which means that what they expected to see was more important than what they actually saw, which was represented by visitors’ satisfaction. Making visitors experience their pre-visit perception will contribute to the sustainability of rural tourism activities benefiting the area.